PENGARUH STRUKTUR KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL TERHADAP KEBIJAKAN HUTANG PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2009-2011 - Bhakti, Adam Dustin (Jurnal Ilmiah Mahasiswa FEB, 2013)
This study has the  objectives to determine the Effect of Managerial and Institutional Ownership of Debt Policy of Manufacture Firms Registered in Bursa Efek Indonesia (Indonesian Stock Exchange). Data being used were financial report of each manufacture company registered in Indonesian Stock Exchange consecutively in 2009-2011. Samples of this study were  55  companies with data completeness. Those data was analyzed using Multiple Linear Regression Analysis.   Calculation showed simultaneous result with F-test and could be concluded that Managerial Ownership and Institutional Ownership has jointly brought negative effect toward Company’s Debt Policy. Partial test results with T-test showed that partially, Institutional Ownership variable has effect toward Company’s Debt Policy.   This variable had negative effect toward Company’s Debt Policy which indicates that increase in institutional ownership would cause decrease in company’s debt. This study result reflected that public corporation in Indonesia has let its stock ownership own by institutional party, thus we could assumed that control of company’s policy would mostly done by institutional ownership. This would made managerial policy in using debt would decrease since there would be strong control element by outsiders thus manager would be very careful in making debt policy.    Keywords: managerial ownership, institutional ownership, company’s debt policy